Community organizing di S.D. Alinsky: pratiche di gestione del conflitto sociale all’interno delle democrazie liberali - Bonichi, Franca (SocietàMutamentoPolitica, 2025)
In recent years, several countries governed by liberal democracies – including Italy – have witnessed the emergence of significant “bottom-up” political initiatives aimed at challenging dominant power structures and advocating for their social redistribution. Many of these initiatives have drawn, either directly or indirectly, on the radical-democratic current of community organizing, founded by sociologist Saul David Alinsky, who was trained in the Chicago School of the 1930s. After years of obscurity, Alinsky’s name resurfaced in public debate, particularly during the election campaigns of Barack Obama and Hillary Clinton – albeit with different connotations. While Clinton’s undergraduate thesis on Alinsky was portrayed as a ‘communist’ precedent from which she sought to distance herself, Obama on several occasions referred to his formative experience as a young community organizer in Chicago, claiming the relevance and effectiveness of such practices, even within the context of an electoral campaign. Community organizing, then – as I will seek to illustrate in these pages – appears to retain significant contemporary relevance, not only as a political practice to counter oligarchic tendencies within our societies, but also as an analytical lens through which to reconsider the profound crisis affecting the political, cultural, and organizational paradigms of liberal democracies.